Soil arthropod diversity, richness, and abundance in agroecological and conventional cotton production systems in Chaco, Argentina - Rojas, Julieta Mariana; Spoljaric, Monica Viviana; González, Julio Rolando; Lacava, Mariángeles; García Hernández, Luis Fernando (Revista Colombiana de Entomología, 2024)
In Argentina, agroecology has grown in last years as a scientific paradigm that seeks to design and evaluate agroecosystems considering sustainability, complexity, and uncertainty. Diversity is a key factor in the design and management of production systems and a necessary component for conservation biological control and the reduction of agrochemicals use. Cotton (Gossypium hirsutum) crop in northern Argentina is usually managed with high load of agrochemicals: agroecological production arises as an alternative. This study evaluated the diversity, richness, and abundance of soil arthropods using pitfall traps in two experimental cotton plots under conventional (CONV) and agroecological management (AE) in Chaco, Argentina. AE system presented higher diversity and richness of predators compared with CONV, even when natural preparations were used for pest control. The phytophagous arthropods showed higher diversity and richness in CONV, even when pyrethroid insecticides were applied for pest control and preventively. The abundance in AE was lower for predators and higher for phytophagous arthropods. Agroecological production of cotton can be a tool that favors conservative biological control and an alternative for areas where protecting the health of farmers and the ecosystem is a priority.